CONTRIBUIÇÕES DA GAMIFICAÇÃO PARA O ENSINO E A APRENDIZAGEM: UMA PROPOSTA DE ENSINO PARA MATEMÁTICA FINANCEIRA - Jacobsen, Daniel de Melo (2018)
The present work aimed to study the techniques relational to gamification and to check the feasibility of implementing a Education and Learning Unit (ELU) Gamificada in the Moodle Platform, with a view to the teaching and learning of concepts of Financial Mathematics. The choice of theme is based on the fact that gamification is based on the elements of the digital games that are currently part of the reality of young people's lives, as well as on the ability of financial education to relate mathematics to students' daily lives. To achieve these objectives, a theoretical study was carried out in order to better understand several aspects related to these themes. Subsequently an ELU was developed in the Moodle Platform, according to the gamification techniques. This ELU was evaluated in front of a class of the Higher Course of Mathematics Degree, IFFAR - Júlio de Castilhos. As data collection instruments we use the participant observation of the researcher and the posting and navigation records of the participants in the Moodle Platform. It was verified that it is possible to implement several gamification strategies through Moodle and that this task requires the teacher to master IT procedures related to: searching, downloading and installing applications; cut and resize pictures; edit texts; and arrange mathematical formulas. It was also observed through the participant observation of the researcher and Moodle activity logs that the gamification techniques used with Moodle confirmed the potential to motivate the participants, in particular those that sought to provide an environment where they could express internal feelings linked to: curiosity, stories related to reality, diversity of options, news and challenges. On the other hand, the repetition of procedures in the activities was negative. We also noticed from the Moodle activity records that the average time spent in training activities was 5 minutes 42 seconds and the number of attempts per activity ranged from 3 to 15. In the acquisition type activities, the number of attempts per activity ranged from 4 to 14, and the score per participant was higher than 70% in 8 of the 10 activities and 60% in the other two activities.